Pregnancy bias toward boys or girls: The Japan Environment and Children's Study. - Shuhei So; Fumiko Tawara; Yu Taniguchi; Naohiro Kanayama; Japan Environment and Children’s Study (JECS) Group (PLoS ONE, 2023)
The sex of the conceived child is a significant concern for parents. To verify whether there women have pregnancy bias toward boys or girls, we investigated whether the history of continuous same-sex pregnancy was associated with the subsequent child's sex. We prospectively analyzed data from the Japan Environment and Children's Study, a birth cohort study. We included all cases of singleton live births (n = 98 412). Women with pregnancy due to infertility treatment were excluded (n = 6255); Similarly, women with a history of miscarriage, artificial abortion, stillbirth, and multiple pregnancies, and those with missing data on the sex of the previous child were excluded. Altogether, 62 718 women were included. For the first live birth, a male-biased sex ratio of 1.055 was observed. Further, no significant difference was found in the sex ratio of the conceived child between women with one boy and those with one girl previously. However, when there were more than two children previously, the subsequently conceived child's male/female sex ratio was significantly higher among boy-only mothers than among girl-only mothers. The results indicated that several pregnant women are biased toward conceiving either boys or girls.